PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. YAMAHA MOTOR ELECTRONICS INDONESIA - Kunto Atmojo; Atang Sudrajat (Sekolah Tinggi Manajemen IMMI Jakarta, 2020)
Productivity in an organization is basically centered on the human resources owned by an organization. Given that human resources are important, attention, direction and management of human resources must be carried out and applied in the organization in order to achieve an organizational productivity goal. organizations need leaders who can direct and develop employee work performance according to the power the leader has towards achieving organizational goals. Based on the reasons above, the writer made a thesis entitled